PARTISIPASI MASYARAKAT DALAM UPAYA KESEHATAN BERSUMBERDAYA MASYARAKAT UNTUK MENINGKATKAN GERMAS DI DESA GUNAKSA - Saraswati, A.A. Sagung Ratu Putri; Lubis, Dinar Saurmauli (ARCHIVE OF COMMUNITY HEALTH, 2020)
ABSTRACT Community-based Health Practice a means of development that uses village funds and is formed based on community needs. The purpose of this research is to find out how the involvement of village community in implementing the UKBM. This study uses a qualitative descriptive research design. Informants this study the Head of Gunaksa Village, BPD, Dawan II Community Health Center Officer, Klungkung District Health Office, Village Health Cadre, and Community Empowerment Office. Data collection techniques used study in-depth interviews and observations. Thematic analysis, validity testing using triangulation source and methods. Community participation in implementation UKBM to improve GERMAS in Gunaksa Village at quasiparticipation (takonism). When planning and evaluating the Village Musrenbang, the involvement of one-way community has no guarantee that community opinion or ideas can be accepted as a form of program change. The results of program decisions in the form of decrees have been planned in Musrenbang are disseminated to the community so the community knows and follows the program. For implementation phase, community involvement in form of posyandu, jumantik, PAUD, anti-smoking cadres, and health facility users. Based on the results, the goverment expected to involve participation of community in planning the program's budget funds at Musrenbang, implementing program, and evaluating program in self-awareness surveys and village community meetings to achieve optimal health programs and can be beneficial to community.